ANALISIS MEKANISME PERPAJAKAN UNTUK MEMENUHI KEPATUHAN WAJIB PAJAK BADAN ATAS PAJAK PENGHASILAN - Yaniar, Mochammad Rifky; Widyawati, Dini (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is motivated by low tax compliance in the submission of obligations as the tax payers. One starting point of acompliance level is the knowledge level of the prevailing taxation law. This research has been carried out by using qualitative research, the data collection technique is done by performing observation, interview technique and documentation techniqueis.Based on the result of the research of analysis of the taxation mechanism of income tax on PT. Wanda Fatimah Zahra most of tax payers are shown as tax payers who comply with the prevailing taxation lawalthoughthere are several issuesthat must be consideredby the company, the taxation mechanism on PT. Wanda Fatimah Zahra from calculating, depositing, up to reporting the income taxhas been running wellin accordancewiththe prevailing taxation laws, the fulfillmentin the submission of payable income tax liability has been implemented safely, practically and easily indepositing and reporting by the company, the comprehension and the knowledge of the taxation mechanisms has become an additional knowledge for PT. WandaFatimahZahra.Keywords:Taxpayer Compliance, Taxation Mechanism, Income Tax